On the effect of the Δ(1232) in hypernuclear non-mesonic weak decay: a microscopic approach - Bauer, Eduardo (2012)
The non-mesonic weak decay of Λ-hypernuclei is studied within a microscopic diagrammatic approach which includes, for the first time, the effect or the δ-baryon resonance. We adopt a nuclear matter formalism extended to finite nuclei via the local density approximation, a one-meson exchange weak transition potential, a Bonn nucleon-nucleon strong potential and a δ. N→ NN strong potential based on the Landau-Migdal theory. Ground state correlations and final state interactions (FSI), at second order in the baryon-baryon strong interaction, are introduced on the same footing for all the isospin channels of one- and two-nucleon induced decays. Weak decay rates and single and double-coincidence nucleon spectra are predicted for CΛ12 and compared with recent KEK and FINUDA data. The δ(1232) introduces new FSI-induced decay mechanisms which lead to an improvement when comparing the obtained nucleon spectra with data, while it turns out to have a negligible effect on the decay rates. Discrepancies with experiment remain only for emission spectra involving protons, but are mostly restricted to double-nucleon correlations in the non-back-to-back kinematics.